2
$\begingroup$

I am reading An Introduction to General Relativity Spacetime and Geometry by Sean Carroll, but simple calculations stop me.

At page 245, a formula for the surface gravity is given $$\kappa^2=-\frac{1}{2}(\nabla_\mu\chi_\nu)(\nabla^\mu\chi^\nu) \tag{6.9}$$ where $\kappa$ is a parameter called surface gravity, $\chi$ is the Killing vector with a Killing horizon.

Can you derive the above formula step by step using Killing's equation $\nabla_{(\mu}\chi_{\nu)}=0$ and the fact that $\chi_{[\mu}\nabla_\nu\chi_{\sigma]}=0$ ? The starting point is the geodesic equation : $\chi^\mu\nabla_\mu\chi^\nu=-\kappa\chi^\nu$.

$\endgroup$
1
$\begingroup$

Starting with $\chi_{[a}\nabla_{b} \chi_{c]} = 0$, we can use the Killing equation ($ \nabla_{b} \chi_{c} = - \nabla_{c} \chi_{b}$) to get,

$\begin{equation} \chi_{c} \nabla_{a} \chi_{b} = -2 \chi_{a}\nabla_{b}\chi_{c} + 2 \chi_{b}\nabla_{a}\chi_{c} \end{equation}$

Contracting both sides with $\nabla^{a}\chi^{b}$, we get (need to use $\chi^{a}\chi_{a} = 0$ on the Killing horizon),

$\begin{align} \chi_{c} (\nabla^{a} \chi^{b})(\nabla_{a} \chi_{b}) &= -2 (\chi_{a}\nabla^{a}\chi^{b})\nabla_{b}\chi_{c} \\ &= -2 \kappa \chi^{b}\nabla_{b}\chi_{c} \\ &= -2 \kappa^2 \chi_{c} \end{align}$

Hence, we obtain,

$\kappa^{2} = -\frac{1}{2} (\nabla_{a}\chi_{b})(\nabla^{a}\chi^{b})$

$\endgroup$
0
$\begingroup$

I don't know why this hasn't been properly answered. Actually, a previous answer was quite confusing in my opinion. From the Killing equation you know that $\nabla_{(a} \chi_{b)} =0$ which means that this derivative is antisymmetric. Therefore, \begin{align} 0&=\chi _{[a} \chi_b \chi_{c]} \\ &= \chi_a \nabla_b \chi_c + \chi_b \nabla_c \chi_a + \chi_c \nabla_a \chi_b\\ \nonumber \therefore \\ \chi_c \nabla_a \chi_b &= -\chi_a \nabla_b \chi_c + \chi_b \nabla_a \chi_c \end{align} where we have used again the Killing equation.

Contracting this with $\nabla^a \chi^b$ and using the geodesic equation for an "inaffine" parameter: $$\chi^a \nabla_a \chi^b = -\kappa \chi^b$$ gives you (after a couple of steps) $$(\nabla^a \chi^b) (\chi_c \nabla_a \chi_b) = - 2 \kappa^2 \chi_c$$ for all $\chi_c$ and thus, you obtain the result you were looking for.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.